Pengaruh Intellectual Capital dan Islamicity Performance Index terhadap Profitabilitas Bank Umum Syariah Periode 2019-2023: Intellectual Capital; Islamicity Performance Index; Profitabilitas; Bank Umum Syariah; Return on Assets (ROA). - Yuliana Sari; Safaah Restuning Hayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to evaluate the extent to which Intellectual Capital and Islamicity Performance Index influence profitability in Islamic Commercial Banks in Indonesia during the period 2019-2023. Profitability by using Return on Assets (ROA). Intellectual Capital is measured through Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), and Capital Employed Efficiency (CEE). Meanwhile, the Islamicity Performance Index is measured through Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), Equitable Distribution Ratio (EDR), Directors-Employees Welfare Ratio (DEWR) and Islamic Income vs Non-Islamic Income (ISIN). This study uses a quantitative method with a panel data regression analysis technique of 45 observations, consisting of 9 banks over a period of 5 years 2019–2023 and applies purposive sampling to obtain samples from Islamic Commercial Banks registered with the Financial Services Authority. The results of the study indicate that HCE, SCE, PSR, ZPR, EDR, DEWR, ISIN have no significant effect and CEE shows a positive effect on profitability. This study is expected to provide insight for Islamic bank management in increasing profitability through optimizing intellectual resources and commitment to sharia goals.